Faktor-Faktor yang Berhubungan dengan Kejadian Berat Badan Lahir Rendah di Puskesmas Kertek 2 Kabupaten Wonosobo: Low Birth Weight Related Factors at Kertek 2 Public Health Centre Wonosobo Regency - Anggit Rizkika; Mohammad Zen Rahfiludin; Alfi Fairuz Asna (Amerta Nutrition, 2023)
Background: Low Birth Weight (LBW) has a negative impact because it may cause infant mortality and other nutritional problems. This research differs from previous research because particular variables are characteristic of agricultural areas and tobacco producers.   Objectives: This study was to analyze the factors associated with low birth weight at the Kertek 2 Public Health Centre.  Methods: It was a quantitative research with a cross-sectional study design. The population was all babies born at the Kertek 2 Public Health Centre, Wonosobo Regency, in 2020. The sample in this study was found using the survey sample size formula with a known N value and was taken using a simple random sampling technique. The independent variables studied in this study included anemia, maternal age, mid-upper arm circumference, maternal weight gain during pregnancy, gestational age, parity, disease and infection, pregnancy interval, exposure to pesticides and smoke, alcohol, economic status, and education. The data were analyzed using Chi-Square and Fisher Exact tests with p-value <0.05. Multivariate data analysis was performed using a binary logistic regression test.   Results: Maternal factors related to LBW were maternal age (p= 0,003), gestational age (p=0,000), parity(p=0,022), and pregnancy interval (p= 0,018). Other factors, such as anemia, upper arm circumference, maternal weight gain, disease and infection, and environmental and socioeconomic factors, did not show a significant relationship. Conclusions: The risk factors for low birth weight at Kertek 2 Public Health Centre were maternal age, gestational age, parity, and pregnancy interval.